Supramolecular structures from structurally persistent and surface active carbon dots in water. Issue 1 (8th December 2022) - Xu, Aoxue; Feng, Ning; Yin, Keyang; Li, Hongguang; Hao, Jingcheng
Abstract : CDs has surface activity to self-assemble in water, forming various supramolecular structures and show good performance in dispersing carbon nanotubes. Abstract : Carbon dots (CDs) have developed into an important class of nanomaterials that have attracted increasing attention during the past decades. Despite numerous types of CDs reported to date, research on their self-assembly is still limited. Herein, we report for the first time the self-assembly of CDs in water, which show concentration-dependent aggregation behavior. The CDs used have a structural motif of a fully carbonized core surrounded by a highly condensed, polymeric network, to which triethylene glycol monomethyl ether (TGME) chains are grafted. When dissolved in water, they show a low critical aggregation concentration (cac) of 0.07 mg mL −1 with the lowest surface tension of ∼37 mN m −1 . Above this cac, nanoclusters and vesicles are observed at relatively low and high concentrations, respectively. At an intermediate concentration, polymorphism is noticed where nanotubes coexist with nanorods. At an elevated temperature, the CDs become more hydrophobic due to the dehydration of peripheral TGME, which decreases the cac and triggers phase transfer from water to toluene. These surface active CDs were used to disperse and stabilize multi-walled carbon nanotubes in water, which showed much better performance than that of both traditional ionic and nonionic surfactants. Our work indicates that with a careful structural design, CDs can be developed into a new type of amphiphiles with properties superior to those of traditional surfactants in specific aspects.